Knowledge Related to the Behavior of Adolescent Girls Regarding Personal Hygiene During Menstruation: Pengetahuan Berhubungan dengan Perilaku Remaja Putri tentang Personal Hygiene pada Saat Menstruasi - Narmin; Tondong, Henrietta Imelda; Batjo, Siti Hadijah; Asrawaty; Lisnawati; Fauziah, Latifah Nur (Poltekkes Kemenkes Palu, 2025)
Background: Hygiene during menstruation is a component of personal hygiene that plays an important role in a person's health behavior status. According to the WHO Regional Office for South East Asia in 2018, individual hygiene and sanitation are number 3 and reproductive health is number 8 in the ten main risk factors for morbidity and mortality in adolescence. Objective: The study aimed to determine the relationship between knowledge and behavior of female adolescents at SMP Negeri 18 Palu City regarding Personal Hygiene during Menstruation. Methods: Analytical survey with a cross-sectional design. The population is 133 female students in grades VII and VIII, and the number of samples is 57; the sampling method is stratified random sampling. The independent variable is knowledge, and the dependent variable is the personal hygiene of female adolescents. The questionnaire is a data collection tool. The analysis used univariate and bivariate methods with the chi-square test. Results: It shows that there is a tendency for well-informed respondents to behave positively in personal hygiene during menstruation, with a p-value of 0.007 (<0.05). Conclusion: This study shows that there is a tendency that adolescent girls who have good knowledge will behave well in maintaining personal hygiene during menstruation at SMP Negeri 18, Palu City